Teaching the scientific literature review collaborative lessons for guided inquiry - Schmidt, Randell K.; Smyth, Maureen M.; Kowalski, Virginia K. (Libraries unlimited guided inquiry series, 2014)
"An essential resource for teachers and librarians who work with students in the later high school years through college and graduate school levels, this book explains and simplifies the scholarly task of researching and writing a scientific literature revie."--Provided by publisher.